Large scale agile transformation - Wyrozębski, Paweł; Cichocki, Hubert (Wybrane aspekty zarządzania procesami, projektami i ryzykiem w przedsiębiorstwach, 2020)
Agile transformation barriers increase with the size of the organization, as well as new, specific for large organizations ones are emerging. The purpose of this article is to discuss issues related to agile transformation in a large organizations, in particular barriers to implementing change. Literature research serves this purpose. Key areas for successful agile transformation include architecture, coordination between teams, scaling process and portfolio management.